KEDUDUKAN ANAK DARI PERKAWINAN SIRI DALAM PEMBAGIAN WARIS MENURUT HUKUM KELUARGA INDONESIA (STUDI PENETAPAN NOMOR 412/PDT.P/2023/PA.JB): The Position Of Children From Siri Marriages In The Distribution Of Heirs According To Indonesian Family Law (Study Number 412/Pdt.P/2023/Pa.Jb - Trianetta Carisa Asral; Khairani Bakri (Faculty of Law, Universitas Trisakti, 2025)
Marriage, according to Law No. 1 of 1974, is a physical and spiritual bond between a man and a woman that must be registered with the state and conducted according to their respective religious teachings. Marriages that do not meet these requirements are considered siri marriages, and children born from such unions are classified as illegitimate children. This study with identification problem about inheritance rights for children born from siri marriages in Indonesian Family Law and reviews Inheritance Ruling No. 412/Pdt.P/2023/PA.JB. Using a normative approach and qualitative analysis, the study result and conclusion that Indonesian Family Law does not explicitly regulate inheritance rights for children from siri marriages. However, Supreme Court Circular No. 3 of 2023 grants them inheritance rights through wasiat wajibah (mandatory will). Based on these findings, Ruling No. 412/Pdt.P/2023/PA.JB is deemed inconsistent with the applicable family law provisions.